Nanopartículas magnéticas de FeCo. Caracterização e estudo de estabilidade após recobrimento com goma de cajueiro (Anacardium occidentale L.) - Oliveira, Maria Karolina da Silva (2019)
Physical and chemical properties inherent of systems in nanometric dimensions make nanoparticles (NPs) highly interesting regarding the production of versatile materials with high potential of applications. This work presents the results obtained for FeCo magnetic NPs covered with polymers of cashew gum (GC) and carboxymethylated cashew gum (CMCG). NPs were synthesized by thermodecomposition of iron and cobalt salts in presence of a reducing agent and the stabilizing agents oleic acid (AO) and oleylamine (OL). Upon transfer to the aqueous medium by using hexadecyltrimethylammonium (CTAB), aliquots were dropped in solution containing the gum of interest. The vibrational spectrum in the infrared region (IR) obtained for the NPs before the polymer immobilization, showed bands typically assigned to the stabilizing and transfer agents indicating the presence of these species on the isolated material (FeCo-AOOL@CTAB). The IR spectra of the NPs covered with the polymers GC (FeCo-AOOL@CTAB@GC) and GCCM (FeCo-AOOL@CTAB@GC) showed bands assigned to the carboxylate groups in the protonated and non-protonated forms. The thermogravimetric analyses allowed to estimate the mass ratio for NP:polymer as 1:3 and 1:1 for FeCo-AOOL@GC and FeCo-AOOL@GCCM, respectively. The stability of the NPs was evaluated in aqueous dispersion and in physiological medium (PBS, pH 7.4) by means of hydrodynamic diameter (DH) and zeta potential (ζ). Although no agglomeration had been observed during 50 h of suspension in these media, the values of DH observed in water for FeCo-AOOL@CTAB@GC and FeCo-AOOL@CTAB@GCCM (459.78 and 231.92 nm) are considerable lower than those observed in PBS (660.47 e 580.9 nm). The more negative values of ζ determined for FeCo-AOOL@CTAB@GCCM (-30 < ζ < -35 mV) in respect to FeCo-OAOL@CTAB@CG (-20 < ζ < -30 mV), are assigned to the higher amount of carboxylate groups in the GCCM polymer. From the values of DH and ζ, it can be concluded that the stability furnished by the GC polymer to the NPs is associated to electrostatic interactions. For the GCCM polymer, besides this interaction, an additional stabilization due to steric hindrance must be taken into account.